(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the effectivity of conventional analgesia and transfascial local bupivacaine infusion used for postoperative pain management on the development of postoperative atelectasisin patients undergoing upper abdominal surgery by midline laparotomy.Materials and Methods: The prospective study included patients that underwent emergency UAS by midline laparotomy and were administered conventional analgesia (CA) (nonsteroidal anti-inflammatory drugs [NSAIDs] + opioids) or transfascial bupivacaine infusion (TBI) (NSAIDs + bupivacaine) following extubating.Results: The groups were similar with regard to age, preoperative ASA status, surgical indications, and operative time (p>0.05). Mean Visual Analogue Scale scores at 0-8, 08-24, and 24-48 h and the requirement of opioids were lower in the TBI group compared to the CA group (p0.05). The median length of intensive care unit stay was significantly lower in the TBI group compared to the CA group (4 and 5 days, respectively) (p0.05).Conclusion: Transfascial bupivacaine infusion/infiltration is effective not only in providing postoperative analgesia but also in the prevention of postoperative atelectasis.Keywords: Transfascial bupivacaine infusion, postoperative atelectasis, postoperative analgesia.